2014
DOI: 10.1093/nar/gku1038
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of polymorphic human nuclear mitochondrial insertions

Abstract: The transfer of mitochondrial genetic material into the nuclear genomes of eukaryotes is a well-established phenomenon that has been previously limited to the study of static reference genomes. The recent advancement of high throughput sequencing has enabled an expanded exploration into the diversity of polymorphic nuclear mitochondrial insertions (NumtS) within human populations. We have developed an approach to discover and genotype novel Numt insertions using whole genome, paired-end sequencing data. We hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
187
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 60 publications
(105 reference statements)
14
187
2
Order By: Relevance
“…They found correlations between the genetic diversity of the NUMTs and their geographical distribution. A more recent large-scale analysis of 23 polymorphic NUMTs was performed by Dayama et al, wherein they established that most of the polymorphic NUMTs were integrated within the past million years [22]. More than 50% of those NUMTs were present in low frequencies (>0.1%), indicating that their insertions were even more recent.…”
Section: Numtogenesis In Health Diversity Disease and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…They found correlations between the genetic diversity of the NUMTs and their geographical distribution. A more recent large-scale analysis of 23 polymorphic NUMTs was performed by Dayama et al, wherein they established that most of the polymorphic NUMTs were integrated within the past million years [22]. More than 50% of those NUMTs were present in low frequencies (>0.1%), indicating that their insertions were even more recent.…”
Section: Numtogenesis In Health Diversity Disease and Cancermentioning
confidence: 99%
“…Yao et al illustrated this concern as the contribution of the NUMTs can often be ignored when some mtDNA mutations are encountered in cancer [106]. Second, the effects of NUMTs and NUMT polymorphisms are often downplayed in studies of mitochondrial heteroplasmy [22, 107], defined as cellular differences in individual mitochondrial genomes due to high rates of mutations [63]. Since mitochondrial heteroplasmy has been implicated in aging and cancer [26, 81], it is the effect of NUMTs is appropriate to minimized on these processes.…”
Section: Numtogenesis In Health Diversity Disease and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…NUMT insertion is a genetically frequent event that is estimated to occur at a rate of ~5 × 10 −6 per germ cell per generation in humans [140]. Although NUMTs have been reported in at least 85 sequenced eukaryotic genomes [139, 141, 142], the exact mechanism(s) of NUMT accumulation in the nucleus is not yet known.…”
Section: Mitochondria In Intracellular Information Transfermentioning
confidence: 99%
“…Although NUMTs are transcriptionally inactive, recent findings have suggested that in mammals integration of NUMTs is non-random [26,27]. The human genome contains NUMT, with mtDNA identities ranging from 64 to 100% [28,29]. We describe this phenomenon of insertion of mtDNA fragments into nuclear genome as ‘ numtogenesis ’.…”
Section: Introductionmentioning
confidence: 99%